Podocytic infolding glomerulopathy: A case report. (1st November 2016) - Kwon, Kye Won; Jeong, Hyeon Joo; Lee, Jang Han
ABSTRACT: Podocytic infolding glomerulopathy (PIG) is a rare glomerular abnormality involving glomerular basement membrane (GBM) bubbling viewable by light microscopy, extensive invagination of the podocytic cytoplasm, and the presence of microstructures viewable by electron microscopy. PIG was proposed as a new disease entity in 2008. However, cases have been reported exclusively in Japan and no case reports outside Japan have been published. Here, we report a case of PIG in a 44-year-old Korean female. The patient showed mild proteinuria without renal functional impairment or other systemic diseases. Glomeruli were normocellular, but GBMs were diffusely and mildly thickened and showed a bubbly appearance with periodic acid methenamine silver (PAMS) staining. Immunofluorescence microscopy showed minimal mesangial IgM deposition, but staining was negative for IgG, IgA, C3, C4, C1q, and fibrinogen. Electron microscopy showed diffuse distribution of microtubules and microspherules within thickened GBM (620–1180 nm). Additional serologic tests revealed positive antinuclear antibodies, but other autoimmune markers were normal or negative. The patient was treated with steroids for three months, after which proteinuria decreased to the normal range.